2017
DOI: 10.1108/sgpe-d-17-00004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding racial/ethnic meaning making

Abstract: Purpose The purpose of this paper is to examine the racial and ethnic aspects of the doctoral socialization to provide a meaningful insight into the belief systems and decision-making processes related to academic success and degree completion. This paper addresses a gap in literature focusing on the racial and ethnic aspects of the doctoral student experience as they relate to student agency. Design/methodology/approach This narrative research of four doctoral students uses a postmodern active interview met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…race and racism) shape minoritized doctoral students socialization experiences (Johnson and Strayhorn, 2022). Azizova and Felder (2017) used socialization as a theoretical approach to examine racial/ ethnic aspects of doctoral socialization and the decision-making processes related to academic success and degree completion in engineering and agricultural sciences. In problematizing and critiquing socialization, they developed four assumptions of doctoral socialization:…”
Section: Socialization Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…race and racism) shape minoritized doctoral students socialization experiences (Johnson and Strayhorn, 2022). Azizova and Felder (2017) used socialization as a theoretical approach to examine racial/ ethnic aspects of doctoral socialization and the decision-making processes related to academic success and degree completion in engineering and agricultural sciences. In problematizing and critiquing socialization, they developed four assumptions of doctoral socialization:…”
Section: Socialization Modelsmentioning
confidence: 99%
“…Azizova and Felder (2017) used socialization as a theoretical approach to examine racial/ethnic aspects of doctoral socialization and the decision-making processes related to academic success and degree completion in engineering and agricultural sciences. In problematizing and critiquing socialization, they developed four assumptions of doctoral socialization: Socialization is a crucial process in doctoral education; Socialization is a meaning making process which may involve racial/ethnic perspectives essential to the ability to engage in the doctoral process; Socialization is shaped by pre-existing culture and value systems; and Socialization is shaped by structural and historical contexts within culture and value systems. …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have documented the structural barriers that shape challenges with motivation and accessibility of professional development resources (Helm et al , 2012; Mitic and Okahana, 2021; O’Meara et al , 2014; Thiry et al , 2008). And some of those barriers may be structural or macro-level, rooted in long-held conceptions of the purpose and process of graduate education and academic cultures of socialization (Andrews et al , 2005; Azizova and Felder, 2017; Bellows and Weissinger, 2004; Helm et al , 2012; Huang et al , 2005; Nerad, 2015b; O’Meara et al , 2014). These discussions on barriers to participation are not limited to the context of US institutions of higher education (Kemp and Kemp, 1999, and Roberts, 2002, for perspectives from Australia and the UK, respectively).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We do so while acknowledging that there are many different sets of these eyes, and not all graduate students experience the academy in the same way. Numerous studies have shown the differential experiences of graduate students and the evolution of professional development needs and career choices throughout their program (Fuhrmann et al , 2011; Helm et al , 2012; Thiry et al , 2015), as well as understandings of how systemic biases including racism, ableism, classism and sexism operate in the academy and shape graduate student experiences (Azizova and Felder, 2017; Blockett et al , 2016; Brunsma et al , 2017; Canetto et al , 2012; Chen et al , 2020; Subbaraman et al , 2020). The interviews we collected reflect a range of these perspectives and experiences, which, taken collectively, have allowed us to explore the volatile space between beliefs and action, the shifting relationships between academia and the “real world” and a reconsideration of the meaning and value of professional development in the present age.…”
Section: Literature Reviewmentioning
confidence: 99%